Dawn song in natural and artificial continuous day: Light pollution affects songbirds at high latitudes. (19th October 2017) - Derryberry, Elizabeth P.
Abstract: In Focus: Da Silva, A., &Kempenaers, B. (2017 ).Singing from North to South: Latitudinal variation in timing of dawn singing under natural and artificial light conditions .Journal of Animal Ecology, 86, 1286 –1297 . doi:10.1111/1365-2656.12739 Satellite images of the world at night show bright dots connected by glowing lines crisscrossing the globe. As these connect‐the‐dots become brighter and expand into more and more remote regions, much of the flora and fauna of the world are experiencing evolutionarily unprecedented levels of light at night. Light cues are essential to most physiological and behavioural processes, and so the need to measure the effects of light pollution on these processes is critical. In this issue, Da Silva and Kempenaers take on this task using an important reproductive behaviour in songbirds—dawn song. The geographic, temporal and taxonomic breadth of sampling in this study allows for a close examination of a potentially complex interaction between light pollution and natural variation in the behaviour of dawn singing across latitude, season and species. Their extensive dataset highlights complexity in how songbirds respond to light pollution. Although light pollution has a strong effect on the timing of dawn song, not all songbirds respond the same way to light pollution, and the effects of light pollution vary with changes in natural light levels. Early dawn singers show more flexibility in the timing of dawn song across the season and across latitudes than late dawn singers, and also appear less affected by light pollution at high latitudes than are late dawn singers. These findings suggest that not all songbirds are responding to artificial continuous daylight as they do to natural continuous daylight, highlighting the general need to measure the fitness effects of light pollution. Abstract : Early dawn singers show more flexibility in timing of dawn song across latitudes and also appear less affected by light pollution at high latitudes than are late dawn singers. These findings suggest not all songbirds respond to artificial continuous daylight as they do to natural continuous daylight.